The effects of vessel approaches on the New Zealand fur seal (Arctocephalus forsteri) in the Bay of Plenty, New Zealand. Issue 2 (30th September 2014) - Cowling, Mary; Kirkwood, Roger; Boren, Laura; Sutherland, Duncan; Scarpaci, Carol
Abstract: Animals that establish new sites near the edge of the species' range may be vulnerable to disturbance as they are low in numbers and are not tied to the sites. Pinniped distributions world‐wide are changing as many species are recolonizing areas of their former ranges and establishing new colonies. Little research is available on the impact that vessel presence may pose on pinnipeds at such sites. This study documents responses of New Zealand fur seals to vessels in the Bay of Plenty, New Zealand, at a recently established breeding colony. Fur seal behavior at the breeding location was recorded in the presence of vessels. GLMM and GAM analyses revealed that fur seal responses varied with month, time of day, duration of vessel exposure, and the distance to the vessel. Age and sex of the seals, and the number of seals present also influenced fur seal response. Fur seals at this site became disturbed when vessels approached to the 10–20 m distance category, and a precautionary minimum approach distance of 50 m has been suggested. This research provides direction for monitoring and minimizing impacts of vessels on fur seals, especially where new sites are being colonized.